Don Vicente Rocafuerte Forger of National Integration - Cordero Aroca, Alberto (Revista Universidad de Guayaquil, 2008)
In February 1833, Don Vicente Rocafuerte returned to his native country, after fulfilling honorable diplomatic functions in Europe in the service of Mexico. His country suffered from the domination of foreign soldiers under the power of the Venezuelan general Juan José Flores. Such a state of affairs had an impact on a man of Rocafuerte’s character who, from an early age, had expanded his intellectuality with travel and studies in contact with figures from the old world that gave him the experience of a true statesman.